2019
DOI: 10.3390/nu11030658
|View full text |Cite
|
Sign up to set email alerts
|

Different Socio-Demographic and Lifestyle Factors Can Determine the Dietary Supplement Use in Children and Adolescents in Central-Eastern Poland

Abstract: Vitamin/mineral supplement (VMS) use has become increasingly popular in children and adolescents; however, different predictors may be associated with their usage. Therefore, the aim of this study was to compare determinants of VMS use in 1578 children and adolescents. Data was collected among parents of children (≤12 years old) and among adolescents (>12 years old) who attended public schools by a self-administered questionnaire. Multivariate-adjusted logistic regression models were used to estimate odds r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…In the case of vitamin D and magnesium, the amounts from VFFs and/or VMSs were negligible (>85% of adolescents did not exceed 20% of DRI), and it would not prevent an inadequate intake (level I and II). Similarly, in our previous survey conducted among school children ( n = 677, 6–12 years), the provided amounts of vitamin D and calcium from VFF were very small ( 11 ). Although in Poland, fat spreads are mandatorily fortified with vitamins A and D, these products are rarely consumed by adolescents; <1/6 of them declared frequent usage of margarines ( 31 ).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In the case of vitamin D and magnesium, the amounts from VFFs and/or VMSs were negligible (>85% of adolescents did not exceed 20% of DRI), and it would not prevent an inadequate intake (level I and II). Similarly, in our previous survey conducted among school children ( n = 677, 6–12 years), the provided amounts of vitamin D and calcium from VFF were very small ( 11 ). Although in Poland, fat spreads are mandatorily fortified with vitamins A and D, these products are rarely consumed by adolescents; <1/6 of them declared frequent usage of margarines ( 31 ).…”
Section: Discussionmentioning
confidence: 64%
“…From specific nutrients, vitamin C was used most frequently (77.6% of VMS-users), while biotin was used least frequently (20.1%) ( Supplementary Table 2 ). The reasons for MVS usage by the group of adolescents (13–20 years old) has been described in detail elsewhere ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it was reported that dietary supplement use was more common in those who used prescription medications and among those who had a diagnosis of chronic headaches among adolescents in the USA [25]. In addition, the presence of chronic disease is associated with dietary supplement use among children in South Korea [24] and Poland [23]. These situation is also reported in adults.…”
Section: Discussionmentioning
confidence: 91%
“…Two European studies evaluated the prevalence and determinants of dietary supplement use in children and adolescents, an important research question given that dietary supplement use has been implicated in preventable adverse drug events and emergency department visits in children and adolescents [21,22]. Data from the KiGGS Module EsKiMo II study showed that around 16% of adolescents in Germany use dietary supplements [9], and data from Eastern Poland reported that around 30% of children and adolescents use vitamin or mineral supplements [23]. Notably, the time frame for which supplement intake was queried was different in these two studies; in Germany the time frame was the previous four weeks and in Poland the past 12 months.…”
mentioning
confidence: 99%